Analisis Gaya Bahasa dalam Album Nelangsa Pasar Turi Karya Bilal Indrajaya : Kajian Stilistika - Zahra, Nasywa Azni Nabila; Muzakka, Moh.; Fadilah, Yuniardi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2025)
This study examines the language style and meaning in Bilal Indrajaya's songs “Saujana,” “Niscaya,” and “Dara,” focusing on how diction, metaphor, personification, and repetition shape lyrical meaning. Using a qualitative, descriptive narrative approach with structural and stylistic theories, the research reveals that simple yet symbolically rich language conveys themes of longing, loss, and hope. The lyrics' rhyme and stylistic elements enhance their musicality and emotional impact, allowing listeners to connect deeply with expressions of love, identity, and emotional pain. Overall, the analysis shows that language style in these lyrics functions both as an aesthetic and as a medium for conveying profound life experiences.Keywords: Language style, Meaning, Structure, Song lyric.